1997
DOI: 10.1099/00207713-47-1-1
|View full text |Cite
|
Sign up to set email alerts
|

A Phylogenetic Analysis of Borrelia Burgdorferi Sensu Lato Based on Sequence Information from the hbb Gene, Coding for A Histone-Like Protein

Abstract: We describe a phylogenetic investigation of Borrelia burgdorferi sensu lato, the causative agent of Lyme disease, based on a DNA sequence analysis of the hbb gene, which encodes protein HBb, a member of the family of histone-like proteins. Because of. their intimate contact with the DNA molecule, these proteins are believed to be fairly conserved through evolution. In this study we proved that the hbb gene is suitable for phylogenetic inference in the genus Borrelia. The hbb gene, which is 327 bp long and enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…The strains used in this study (Table 1) belong to five species endemic to Europe, B. burgdorferi s.s., B. garinii, B. afzelii, B. valaisiana and B. lusitaniae. Information regarding DNA-DNA reassociation was available for each of these strains (Postic et al, 1990;Baranton et al, 1992;Canica et al, 1993;Le Fleche et al, 1997;Wang et al, 1997) and sequences at several of the selected loci were accessible from the literature or databases (Postic et al, 1994;Le Fleche et al, 1997;Valsangiacomo et al, 1997;Wang et al, 1997;Casati et al, 2004;Park et al, 2004). For the delineation of 'B.…”
Section: Methodsmentioning
confidence: 99%
“…The strains used in this study (Table 1) belong to five species endemic to Europe, B. burgdorferi s.s., B. garinii, B. afzelii, B. valaisiana and B. lusitaniae. Information regarding DNA-DNA reassociation was available for each of these strains (Postic et al, 1990;Baranton et al, 1992;Canica et al, 1993;Le Fleche et al, 1997;Wang et al, 1997) and sequences at several of the selected loci were accessible from the literature or databases (Postic et al, 1994;Le Fleche et al, 1997;Valsangiacomo et al, 1997;Wang et al, 1997;Casati et al, 2004;Park et al, 2004). For the delineation of 'B.…”
Section: Methodsmentioning
confidence: 99%
“…Haplotype 28 grouped with CA2, an unclassified Borrelia sp. that previous studies found forms a group distinct from B. burgdorferi s.s. based on DNA-DNA hybridization and sequencing analyses (Valsangiacomo et al, 1997;Postic et al, 1998). Haplotypes 29 and 30 grouped with an uncharacterized Borrelia sp.…”
Section: Haplotype Diversitymentioning
confidence: 99%
“…In the meantime, DNA-DNA hybridization and some useful gene fragments are used for elucidating genetic relationships or in phylogenetic studies. Such gene fragments include genes for rRNAs (Woese, 1987), the β-subunit of ATPsynthase (Amann et al, 1988), tRNA (Hofle, 1990), glutamine synthetase (Brown et al, 1994), elongation factor Tu (Kamla et al, 1996), a 65 kDa heat-shock protein (hsp65) (Swanson et al, 1997) and a histonelike protein (hbb) (Valsangiacomo et al, 1997 The GenBank accession numbers for the sequences of the RNase P RNA genes determined in this study are listed in Table 1. these, 16S rRNA or 16S rDNA have been extensively studied and have become important as target genes in the phylogeny and classification of prokaryotic organisms (Woese & Fox, 1977 ;Woese, 1987 ;Stackebrandt et al, 1997). Nevertheless, there is a general consensus that 16S rRNA gene sequences may be inappropriate for elucidating the relationships between closely related organisms and may be insufficient to guarantee species identity (Fox et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…In the meantime, DNA-DNA hybridization and some useful gene fragments are used for elucidating genetic relationships or in phylogenetic studies. Such gene fragments include genes for rRNAs (Woese, 1987), the β-subunit of ATPsynthase (Amann et al, 1988), tRNA (Hofle, 1990), glutamine synthetase (Brown et al, 1994), elongation factor Tu (Kamla et al, 1996), a 65 kDa heat-shock protein (hsp65) (Swanson et al, 1997) and a histonelike protein (hbb) (Valsangiacomo et al, 1997) Abbreviations : LL-A 2 pm, LL-2,6-diaminopimelic acid ; ITS, internally transcribed spacer.…”
Section: Introductionmentioning
confidence: 99%